Potential benefits of Cuminum cyminum L supplementation on components of metabolic syndrome in adults with metabolic disorders: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Liu, Man; Wu, Songze; Falahatzadeh, Maryam (Frontiers in Nutrition, 2026)
IntroductionCumin (Cuminum cyminum L.) is recognized for its anti-diabetic, anti-inflammatory, and antioxidant properties, which may influence components of metabolic syndrome (MetS) in adults with metabolic disorders. However, previous studies have reported inconclusive and sometimes conflicting results. Therefore, this meta-analysis aimed to evaluate the effects of cumin supplementation on MetS components in adults with metabolic disorders.MethodsA systematic search of electronic databases, including Web of Science, Scopus, Embase, and PubMed, was conducted up to April 2025 to identify randomized controlled trials (RCTs) evaluating cumin supplementation in adults with metabolic disorders. Subgroup and sensitivity analyses were performed to explore heterogeneity. The search was restricted to studies published in English. Publication bias was assessed using Begg’s test.ResultsA total of nine studies published between 2013 and 2020, with intervention durations ranging from 8 to 24 weeks, were included in the meta-analysis. The results indicate that cumin supplementation significantly affected several components of MetS. Specifically, cumin demonstrated a significant reduction in fasting blood sugar (FBS) (SMD: −1.38; 95% CI: −2.26 to −0.50, p = 0.002; I2 = 94.6%, p < 0.001), triglycerides (TG) (SMD: −0.58; 95% CI: −1.14, −0.02, p = 0.044; I2 = 88.7%, p < 0.001), and waist circumference (WC) (SMD: −0.46; 95% CI: −0.87, −0.04, p = 0.033; I2 = 56.1%, p = 0.077). Additionally, cumin was associated with a significant increase in high-density lipoprotein cholesterol (HDL-C) (SMD: 0.77; 95% CI: 0.02 to 1.52, p = 0.045; I2 = 92.3%, p < 0.001). Furthermore, subgroup analysis revealed that cumin could have more beneficial effects in older adults (>50 years old) in term of FBS and TG. Also, lower doses of cumin supplementation were responsive for improvement in FBS and HDL-C levels.ConclusionThis meta-analysis suggests that cumin supplementation may have beneficial effects on several components of MetS, including FBS, lipid profile (TG and HDL-C), and WC, in adults with metabolic disorders. However, further high-quality, large-scale trials are needed to strengthen the evidence and confirm these findings.